2011
DOI: 10.1111/j.1365-2621.2010.02541.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant extracts on lipid oxidation during frozen storage of minced fish muscle

Abstract: The aim of the study is to determine the effect of pomegranate seed extract (PSE) and grape seed extract (GSE) addition to chub mackerel minced muscle on lipid oxidation during frozen storage. Each extract was added to minced fish muscle at 2% concentration and then stored at )18°C for 3 months. The effect of plant dietary fibres to control lipid oxidation was compared with untreated samples (control). Formation of lipid hydroperoxides and thiobarbituric acid-reactive substances (TBARS) was significantly inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
(53 reference statements)
5
14
0
3
Order By: Relevance
“…The addition of GPF darkened the samples and this browning (< L *) was higher ( p < .05) when the GPF concentration was increased from 1% to 2%. Similar trend in color parameters was observed in groundfish (mackerel, Scomber japonicus ) added with grape extract (Özalp Özen et al, ). Selani et al () also verified the browning of the chicken samples with the addition of Isabel grape extract.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The addition of GPF darkened the samples and this browning (< L *) was higher ( p < .05) when the GPF concentration was increased from 1% to 2%. Similar trend in color parameters was observed in groundfish (mackerel, Scomber japonicus ) added with grape extract (Özalp Özen et al, ). Selani et al () also verified the browning of the chicken samples with the addition of Isabel grape extract.…”
Section: Resultssupporting
confidence: 76%
“…However, there are still some technological hurdles in the development and commercialization of minced fish. Fatty fishes, such as salmon, contain high contents of polyunsaturated fatty acids (PUFA), which are susceptible to oxidation, especially in minced fish, which enhances the deterioration of flavor, color, texture, and nutritional value (Özalp Özen, Eren, Pala, Özmen, & Soyer, ). Lipid oxidation in minced muscle of fatty fish muscle is the most significant problem in quality preservation during frozen storage and can be delayed by adding antioxidants, either natural, such as phenolic compounds, or synthetics, such as BHT—2,6‐ditercbutyl‐ p ‐creso‐ (Sánchez‐Alonso, Jiménez‐Escrig, Saura‐Calixto, & Borderías, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the antioxidant agent decreased oxygen gas to interact with fish fillets which inhibited the oxidization. Earlier studies have shown similar results that protein and lipid oxidization were delayed by adding extracts of plants (Gokoglu et al, ; Öz, ; Özalp Özen et al, ).…”
Section: Resultssupporting
confidence: 57%
“…It is important to note that the amount of hydroperoxides that we found in the fish muscle samples following 3 d of refrigerated 4°C storage (11.8 6 1.3 mmol linoleic hydroperoxide/g fat) is equivalent to a level of off-flavors classified as ''incipient rancid'' (14,15). Such subthreshold rancidity is commonly present in many commercial, frozen fish products as well as in fatty food products stored for long periods of time or at insufficiently low temperatures (13).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is likely overlap between the oxidation products formed during digestion and those formed during food storage; e.g., in fish, the lipoxygenases, hemoproteins, and PUFA substrates are present, albeit at different ambient conditions, in food storage and during digestion. It is also important to note that although food that develops high amounts of oxidation products during storage may be discarded due to poor odor, common storage conditions may lead to the development of ''incipient rancid'' odors that can be masked by food flavors (14,15). Moreover, the further development of oxidation products within the gastrointestinal tract would not be detected.…”
Section: Introductionmentioning
confidence: 98%